Fetal counseling for congenital heart disease: is communication effective?. (12th December 2022) - Holmes, Kathryn W.; Huang, Jennifer H.; Gutshall, Kristine; Kim, Amanda; Ronai, Christina; Madriago, Erin J.
Abstract: Purpose: To assess the accuracy of maternal understanding of fetal cardiac defects following initial fetal counseling. Methods: Pregnant women with a fetal diagnosis of congenital heart disease (CHD) were surveyed regarding understanding of their fetus's heart defect. The survey asked: (1) for a description of the heart condition; (2) how confident they were in the diagnosis; (3) whether their fetus would require heart surgery. Two fetal cardiologists evaluated the maternal qualitative description. Partners were excluded from the study. Results: Fifty-one participants consented and 39 completed the survey. Mean age was 31 years, 60% had some college level or post-graduate education, 48% had Medicaid insurance, and 81% were Caucasian. More than three-quarters of participants, stated they had either "quite a bit" or "very much" understanding of their fetus's diagnosis. Maternal assessment matched the physician's assessment of accuracy with 77% ( N = 30) demonstrating either "quite a bit" or a "very accurate" description of the diagnosis. All women correctly understood if their fetus would require heart surgery. Highest level of maternal education positively correlated with the accuracy of diagnosis (regression coefficient 0.48, p < .002). However, confidence in the diagnosis was independent of both education (0.30, p = .167) and maternal age (−0.03, p = .234). Conclusions: Fetal counseling is effective in conveying anatomy and the need for surgery; however, accuracy amongst women with lower levels of education and maternal confidence in understanding can be improved.